CD8+ encephalitis: a severe but treatable HIV-related acute encephalopathy. Issue 1 (1st November 2016) - Zarkali, Angeliki; Gorgoraptis, Nikos; Miller, Robert; John, Laurence; Merve, Ashirwad; Thust, Stefanie; Jager, Rolf; Kullmann, Dimitri; Swayne, Orlando
Abstract : Rapidly progressive encephalopathy in an HIV-positive patient presents a major diagnostic and management challenge. CD8+ encephalitis is a severe but treatable form of HIV-related acute encephalopathy, characterised by diffuse perivascular and intraparenchymal CD8+ lymphocytic infiltration. It can occur in patients who are apparently stable on antiretroviral treatment and probably results from viral escape into the central nervous system. Treatment, including high-dose corticosteroids, can give an excellent neurological outcome, even in people with severe encephalopathy and a very poor initial neurological status. We report a woman with CD8+ encephalitis, with a normal CD4 count and undetectable serum viral load, who made a good recovery despite the severity of her presentation.